PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERKALIAN KELAS III SD NEGERI LAMTEUNGOH ACEH BESAR - Diandita, Elly Rizki; maulina, Cut; Azkia, Nura; Khairunnisa, Fira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education plays an important role in improving the quality and potential of students. Learning outcomes are systematic efforts made to improve the abilities, knowledge, skills, and attitudes of students in order to achieve learning objectives optimally. Therefore, the discovery learning model is used as an alternative to improve understanding and learning outcomes in mathematics. Based on the background, the formulation of the problem in this study is: Can the application of the discovery learning model improve student learning outcomes in multiplication material in grade III of Lamteungoh State Elementary School? This study aims to improve student learning outcomes in multiplication material in grade III of Lamteungoh State Elementary School. The method used is a quantitative method involving 16 students as research samples. Data were collected through observation, tests (pretest and posttest) and documentation. Data analysis was carried out using the n-gain test, and the paired sample t-test. With the help of the SPSS version 27 and excel applications. If the sig α value <0.05, then reject H₀ → meaning there is an increase in understanding of the concept of multiplication. If the sig α value > 0.05, then accept H₀ → meaning there is no significant increase. The results of the study showed an increase in the average value from the pretest of 25.56 to the posttest of 33.81, with an N-Gain value of 0.52 in the moderate category. Hypothesis testing using a paired sample t-test showed a significant difference (sig α < 0.05), so the discovery learning model has a positive effect on student learning outcomes.